2010
DOI: 10.1088/0029-5515/50/8/084004
|View full text |Cite
|
Sign up to set email alerts
|

Fast-ion losses induced by ACs and TAEs in the ASDEX Upgrade tokamak

Abstract: The phase-space of convective and diffusive fast-ion losses induced by shear Alfvén eigenmodes has been characterized in the ASDEX Upgrade tokamak. Time-resolved energy and pitch-angle measurements of fast-ion losses correlated in frequency and phase with toroidal Alfvén eigenmodes (TAEs) and Alfvén cascades (ACs) have allowed to identify both loss mechanisms. While single ACs and TAEs eject resonant fast-ions in a convective process, the overlapping of AC and TAE spatial structures leads to a large fast-ion d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…TAEinduced losses have also been observed on JET and ASDEXUpgrade [9][10][11]. Similar to the fast-ion losses by fishbones and sawteeth, the TAE-induced losses are explained in terms of particles phase-locking with the mode and experiencing convective losses due to outward E × B drifts.…”
Section: Introductionmentioning
confidence: 76%
“…TAEinduced losses have also been observed on JET and ASDEXUpgrade [9][10][11]. Similar to the fast-ion losses by fishbones and sawteeth, the TAE-induced losses are explained in terms of particles phase-locking with the mode and experiencing convective losses due to outward E × B drifts.…”
Section: Introductionmentioning
confidence: 76%
“…[1][2][3][4][5][6][7][8][9] The losses were measured using a Fast Ion Loss Detector (FILD) with a high frequency response and were coherent with the Alfv en eigenmodes. It was shown that the coherent losses in DIII-D mainly come from trapped particles whose orbits are close to the tokamak wall.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] RSAEs cause fast-ion transport. [4][5][6][7] They also provide accurate information about the evolution of the q profile: When q min is an integer value, a "grand cascade" of many RSAEs with different toroidal mode numbers n is often observed. 2 In the laboratory frame, the frequency x of an RSAE is approximately 8 x…”
Section: Introductionmentioning
confidence: 99%
“…In the vast majority of published cases, [1][2][3][4][5][8][9][10][11][12][13][14][15][16][17][18][19][20][21] the modes first appear when q min ¼ m=n, then the mode frequency sweeps upward in frequency as the q profile evolves. Very rarely, 8,22,23 a mode will sweep downward to the minimum frequency, then sweep upward in the normal fashion.…”
Section: Introductionmentioning
confidence: 99%